ORIENTASI BENTUK KHIYAR PADA MAHASISWA HUKUM EKONOMI SYARIAH INSTITUT AGAMA ISLAM NEGERI (IAIN) PONTIANAK PASCA BERTRANSAKSI E-COMMERCE - Umi Qanuni; Rasiam Rasiam; Rahmat Rahmat (LP2M and Shariah Faculty of The Pontianak State Institute of Islamic Studies, 2021)
This study aims to find answers to the main problem, namely how to practice E-commerce on Shariah Economic Law students and the orientation of their khiyar forms after e-commerce transactions. This research is a type of legal research, while the data collection technique uses primary data from observations, interviews, and transaction document reports. Then, secondary data used by researchers are books, results of previous studies, articles, and journals. The data analysis technique is the stage of data reduction and drawing conclusions. Based on the results of the study, it can be concluded that the 15 students who interviewed researchers, 4 of whom had received goods that were not according to the order. Regarding the orientation of khiyar on Shariah Economic Law students at IAIN Pontianak after e-commerce transactions, it is a khiyar disgrace (khiyar aib). Khiyar disgrace is included in the type of khiyar naqisah (reduced value of goods offering). Keywords: E-commerce, Khiyar Disgrace, Law Student